Carbon accumulation and aggregate stability in an Acrisol under different fallow management in Ghana - Dowuona, G. N. N.; Adjetey, E. T.; Nartey, E. K.; Adjadeh, T. A.; Heck, R. (Global Journal of Food and Agribusiness Management, 2012)
Soil organic carbon (SOC) in relation to aggregate stability, plant biomass accumulation and other properties of a Ferric Acrisol under different fallow management practices was determined to ascertain their potential for sequestering carbon. Three minor season fallow treatments replicated four times were natural and burning (T1), natural and plough-in (T2), pigeon pea (T 3), bare land (T 4), cowpea (T5), mucuna (T6) and natural and fertilized cropped (T 7).Inherent nutrient status of the soil was low. Generally, dry matter (DM) yield increased for all the treatments in the minor season of 2006 more than in 2005. A high DM yield for T3 resulted from the shrubby and semi-woody nature of pigeon pea.Moisture stress from low rainfall decrease DM yield in 2007. In 2005, SOC contents of the treatment plots were lower than the initial amount although, T3 produced relatively the highest SOC accumulation (20,293 ± 326 kg C ha-1 ). In 2006, the legume-amended treatments (T3, T5 and T6) had similar SOC contents as the control (T4); the lower SOC contents in the natural fallow plots confirmed the negative effect of burning, especially in T1. Soil OC accumulation was greater in 2007 than in 2006 (except for T4). Water dispersible silt fraction decreased with increasing SOC accumulation (r value = - 0.88**). Dispersion ratios, more related to SOC (R2 value of -0.95** in the natural fallows and - 0.76* in the legume fallows), generally decreased from an average of 0.88 in 2006 to 0.50 in 2008 emphasizing the positive role of aggregate stability in SOC accumulation